PEMERINTAHAN YANG CERDAS YANG DIBUTUHKAN DALAM REVOLUSI INDUSTRI 4.O - Redjo, Samugyo Ibnu (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2019)
The future government is a digital government that relies on the ability of E. Govt. (electronicgovernment) and it is impossible to avoid it. Advances in science, communication technology andinformation and the development of the economy and trade. Cause the Government is faced with anincreasingly liberal and individualist mass of people who tend to deny the existence and grandeur ofculture and religion. It is also necessary to understand that the social transformation experienced by"the West" originated from agriculture (first wave), industry (second wave), and information ( thirdwave), as Alvin Toffler stated in Future Shock and The Third Wave occurring in third world countriessimultaneously, no exception in Indonesia. This causes the Indonesian people to be in the three waves,so naturally the development development must be based on the indications of the three waves. 4.OIndustrial Revolution, is indicated by the development of global information that has swept andspread globally which has caused third-world societies, including Indonesia, to be in a transition ofvalues. The values of the industrial society and the values of the information society have not grownand are adaptive in people's lives, while the values of tradition have gradually been abandoned. Asa result, the size of a society's assessment of a problem tends to be multi-dimensional and highlydependent on those who are able to benefit economically as measured by the appearance ofmaterialism.